Pendampingan Pembentukan Pos UKK Nelayan Di Desa Tanjung Banun Kota Batam Tahun 2023 - Noviyanti Yanti; Leni Utami; M. Kafit (COVIT (Community Service of Health), 2023)
Occupational Health Effort Post (UKK Post) is a form of Community-based Health Effort (UKBM) and is a form of community empowerment in informal worker groups, in terms of preventive and preventive efforts to protect workers from occupational diseases and free from health problems healthy life. Community service aims to provide assistance in the formation and implementation of independent and sustainable UKK Post activities in Tanjung Banun Village, Batam City. This community service activity method is carried out with a Focus Group Discussion (FGD) agenda with the Fisherman Community. In general, the results of community service activities are the formation of an organizational structure for the UKK Post along with clear duties and responsibilities, the formation of Occupational Health Cadres, the availability of the UKK Post, the availability of First Aid boxes containing basic medicines and medical equipment and the Galang Health Center UPT as a facilitator in the Development of the UKK Post in Tanjung Banun Village, Batam City. The conclusion is the need for the puskesmas as a facilitator in carrying out the activities of the UKK Post and the participation of fishing communities as a resource in the establishment of the UKK Post. Keywords: Assistance, Establishment, UKK Post, Fishermen